SOFT SYSTEM METHODOLOGY FOR GREEN BUILDING DESIGN CONCEPTS FOR COMPLYING BUILDING REGULATION IN INDONESIA - Sutikno; Hendrik Sulistio; Sarwono Hardjomuljadi (Operational Research in Engineering Sciences: Theory and Applications, 2024)
In order to adhere to the green building regulations established by the Minister of Public Works and Public Housing of the Republic of Indonesia, it is imperative to employ methods aimed at fostering awareness of the inherent advantages and positive effects associated with green buildings in the context of new construction. Unfortunately, the anticipated conversion of new construction projects into green buildings is not progressing as intended. Issues pertaining to planning, execution, utilization, and oversight, encompassing organizational considerations, financial aspects, and community engagement, have emerged as significant impediments. This situation perpetuates a misconception among the general public that investments in green building initiatives are prohibitively expensive. A primary challenge is the absence of explicit standards for green building investments, coupled with the inefficiency of gradually implementing reference terms within budgetary constraints. Previous research indicates that a holistic approach, aligning green building design with principles of sustainability and sustainable development, represents an optimal strategy to address these challenges. This work seeks to investigate how the principles of sustainable green building design can align with the requirements stipulated by the Minister and the Housing Regulation of the Republic of Indonesia. This endeavour involves integrating theoretical concepts with value engineering and life cycle cost assessment through the application of the soft system methodology in an action research framework. The outcome will be a theoretical framework that encapsulates initiatives, providing guidance for diverse strategies in green building practices that prioritize both sustainability and cost-effectiveness. The author underscores the importance of recognizing the dedication and knowledge required to comprehend that the expenses associated with constructing green buildings are outweighed by the substantial benefits achievable.